Increasing Student Motivation in Learning English Through Digital Ice-Breaking Activities - Irfani, Moch; Ma’rifatulloh, Sayid (Journal of English Language and Education, 2025)
In this digital era, students often lack motivation in conventional English learning. Although ice-breaking is found to be helpful, conventional methods can feel monotonous for students who are familiar with digital technology, and the impact of digital ice-breaking has not been widely explored. This study aims to determine the effectiveness of digital ice-breaking (using platforms such as Bamboozle, Kahoot! and Quizizz) on the learning motivation of eighth-grade students at SMP Negeri 1 Diwek. A pre-experimental design with one pre-test/post-test group was used on 31 eighth-grade students in class C. Motivation was measured using a questionnaire before (pre-test) and after (post-test) the digital ice-breaking treatment. The results showed a statistically significant difference (p = 0.009) between the pre-test motivation scores (mean = 30.29) and post-test scores (mean = 33.36). The Paired Samples T-test (t = -2.790) and moderate effect size (Cohen's d = -0.501) confirmed the positive impact of the treatment. Digital ice-breaking proved to be effective in increasing students' motivation in learning English.